STUDI KUANTITATIF KORELASI ASPEK IBU DAN BALITA TERHADAP KEJADIAN STUNTING - Pratami, Intan Monik; Yulidar, Elfina; Wirawan, Susilo; Indriani, Farihah (Ensiklopedia of Journal, 2025)
Abstract: Stunting is one of the nutritional problems that remains a serious challenge in efforts to improve the nutritional status of children in Indonesia. This condition is characterized by impaired linear growth, where children have a shorter height than their peers. The purpose of the study was to determine the correlation between maternal and toddler aspects of the incidence of stunting. The research design used in this study was case control. The research was conducted in the Kluwut Health Center working area. The research was conducted in July 2023. The study population was all toddlers aged 24 to 59 months whose data were recorded at the Kluwut Health Center. The sample amounted to 98 toddlers consisting of 49 cases and 49 controls. The sampling technique used in this study was non probability sampling with purposive sampling method. Data analysis was done univariate and bivariate. The results showed that there was an association between the history of MP breastfeeding (p value: 0.01) and the history of LBW (p value: 0.001) on the incidence of stunting. It is recommended that mothers who have toddlers be able to increase their children's animal protein intake by modifying animal protein food ingredients into forms and flavors that children prefer so that children are more interested and not bored with the side dishes provided and health centers to optimize socialization programs for pregnant women to prevent LBW and stunting so that every family member has good nutritional status including children.Keywords: Underweight, LBW, breastmilk MP, stunting.